Cytocompatibility of UV and visible light photoinitiating systems on cultured NIH/3T3 . broblasts in vitro - Bryant, S.J.; Nuttelman, C.R.; Anseth, K.S.
This work investigates the cytocompatibility of several photoinitiating systems for potential cell encapsulation applications. Both UV and visible light initiating schemes were examined. The UV photoinitiators included 2,2-dimethoxy-2-phenylacetophenone (Irgacure 651), 1-hydroxycyclohexyl phenyl ketone (Irgacure 184), 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)- 1-propanone (Irgacure 907), and 2-hydroxy-1-[4-( hydroxyethoxy)phenyl]-2-methyl-1-propanone (Darocur 2959). The visible light initiating systems included camphorquinone (CQ)with ethyl 4-N,N-dimethylaminobenzoate (4EDMAB)and triethanolamine (TEA)and the photosensitizer isopropyl thioxanthone. A cultured . broblast cell line, NIH/3T3, was exposed to the photoinitiators at varying concentrations from 0.01
Keywords: CYTOCOMPATIBILITY; PHOTOPOLYMERIZATION; TISSUE ENGINEERING; CELL ENCAPSULATION; PHOTOINITIATORS